Moravia l’africano delle Storie della preistoria - Nicewicz-Staszowska, Ewa (Bergen Language and Linguistics Studies, 2019)
In 1976 Alberto Moravia, then sixty-nine years old, won the Andersen Prize for the Mustafà, la volpe del Sahara, his first children’s tale. Then followed the stories about others humanized animals, first published in the “Corriere della Sera” and in the various editions of selected stories, and later collected in the volume Stories of Prehistory (1982), which brought Moravia the Viareggio Prize in 1983. Apart from the deep affection that Moravia felt for animals and nature in general, that form of narrative has its roots in the numerous African journeys he undertook since 1962. For Moravia, the Black Continent, “the most beautiful thing that exists in the world”, was an artistic discovery and an “antidote to the highly refined, sophisticated and mechanical civilization”. Africa, a place “still amid prehistory and history”, was for him – as in some respects it was for Pasolini – the depository of primordial values in the process of disappearing, due to the imminent industrialization. In the Stories of Prehistory Moravia speaks of those universal values, always opposed to the vices, and views them through curiosity that is usually inaccessible to adults. His children’s tales – always funny, sometimes hilariously merciless – occupies a separate position within the oeuvre of the Roman writer and gained him many fans. The aim of this paper is to provide an overview of those aspects of Moravia’s work which have not been reflected yet and are still very relevant today.